Conception, Scientific And Re-Methodology Pesantren Sunan Drajat In Developing Islamic Education-Based Learning Output - Ahdar Ahdar; Musyarif Musyarif; Aris Muttaqin (Didaktika Religia, 2020)
This study seeks to explain the Islamic education development strategy based on the output (output) in Pesantren Sunan Drajat, East Java. This study is very important, considering the main issue of Islamic education today is its output where to go in the development of industry and technology. Many people judge if output Islamic educational institutions are not able to compete with other educational institutions. So in this study, I will expose the antithesis of all the criticism that comes. The method used in researching is a descriptive qualitative analytic approach. It is taken directly from your data source field as the primary data by purposive sampling. This research concludes several things, including: first, the design of Pesantren Sunan Drajat is oriented towards two things; potential development of students as scientists and economists and prepare competent graduates of the schools to be healthy and competent at the development of the industrial era. Second, schools apply four methods of seed; 1) The flipped classroom method. 2) methods cooperative system. 3) corporate methods of rule. 4) The simulation method of practice. Third, to prepare a well-established and competitive output, then boarding apply two strategies; placing its graduates as the successor to struggle in the company and take advantage of the boarding business partner network to use the services of graduates as a capable force.